Detailed experimental and numerical analysis of hydrodynamics in the outflow measurement channel of a sewage treatment plant. Issue 4 (15th June 2022) - Ragessi, I. Matias; García, Carlos Marcelo; Damian, Santiago Marquez; Tarrab, Leticia; Patalano, Antoine; Rodriguez, Andres
Abstract: The 'Bajo Grande' Wastewater Treatment Plant has a design capacity of 2.78 m 3 /s, and discharges into the Suquia River (Córdoba, Argentina). The river has an average flow rate of 10 m 3 /s, with lower values during the summer. Currently, the treatment plant does not have an accurate discharge-measurement system prior to the discharge into the river, which makes it difficult to evaluate the dosing of the disinfection treatment. The outflow rate is measured in a straight flume. However, at the inlet section of the flume, a 180° sharp bend induces a complex turbulent flow with instabilities and low-frequency velocity fluctuations which are not appropriate for flow quantification. In this type of flow, most of the in situ flow discharge-measurement systems have great uncertainty. Therefore, in situ flow measurements with an Acoustic Doppler Current Profiler, Large-Scale Particle-Tracking Velocimetry techniques and a prototype-scale Detached Eddy Simulation model were combined to obtain a detailed characterization of the turbulent flow. The results provide flow rates, fields of mean flow velocity, temporal evolution, and characteristic parameters of the turbulence. This allowed a better understanding of the effects of turbulence and flow instabilities. The results provide a basis to validate numerical models used in the hydraulics design of contact chambers to improve the disinfection process. HIGHLIGHTS: The work focuses on the study of a complex turbulent flow, with flow instabilities and low-frequency fluctuations. An Acoustic Doppler Current Profiler and Large-scale Particle Image Velocimetry (LS-PIV) were applied to characterize turbulent flow in a prototype-scale contact chamber. DES simulation was used to detailed characterization of a complex turbulent flow; particularly, the spatial and temporal evolution. Graphical Abstract